Work from home and firm productivity: The role of ICT and size - Filippo Boeri; Riccardo Crescenzi; Davide Rigo (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2025)
This paper investigates the impact of post-pandemic adoption of work from home (WFH) on firm productivity. The paper uses administrative firm-level data covering the universe of remote workers in Italy and leverages exogenous pre-pandemic variation in firm-specific access to fibre broadband as an instrument. We find that WFH had a large negative impact on productivity during the pandemic. However, larger firms and those with prior ICT investments mitigated these losses. In the longer term, the impact of WFH on productivity is no longer significant. Yet, we find suggestive evidence that firms employing highly qualified workers experienced productivity gains.
Keywords: D22; J21; J24; L25; O33; 330; work from home; firms; productivity